Corelația interesului privat cu instituția licențierii activității de întreprinzător [Articol] - Pascaru, Nicolae (Academia de Administrare Publică, 2022)
This article aims at a complex analysis of the concept of private interest and its identi cation both in the regulations of the national legal framework and of other countries, as well as the doctrinal treatment of this concept in the legal literature. The concept of private interest is closely related to the concept of public interest and the licensing of entrepreneurial activity, where the public interest is nothing more than a collection of private interests and the licensing of certain activities is designed to protect the public interest. The legal regulations in which we identify the concept of private interest, are intended to protect the individual, the legal entity, the entrepreneur and any subject of legal relations, from excessive, sometimes abusive intervention by the state in the licensed activity of entrepreneurs. Thus, the private interest is as a guarantor of non-interference in the activity of private subjects to practice a certain licensed activity. At the same time, the combination of private and public interests represents a new paradigm of state regulation of the economy in general, including licensing entrepreneurial activities in particular.
CORRELATION OF PRIVATE INTEREST WITH THE INSTITUTION OF ENTREPRENEURSHIP
Keywords: private interest; public authority; entrepreneurial activity; interes privat; autoritate publică; activitate de întreprinzător